The Way Forward for Elective Surgery in Developing Countries: Day Case Surgery - Wismayer, Richard (New Frontiers in Medicine and Medical Research Vol. 14, 2021)
The established principle of ambulating surgical patients as early as possible lies behind the concept of day case surgery currently being practised worldwide. There is a lag in day surgery practise between the developed and the developing world. In the last decades, freestanding and autonomous day surgery units have been established in the developed world however the developing world still tends to practise hospital based day case surgery. The purpose of this review is to popularize the concept of day case surgery in developing countries, decreasing morbidity and mortality from elective surgery patients and providing valuable bed services to emergency surgical patients. This review examines the practise of day surgery in developing countries and reviews the scope, organization and the necessary standard for practising day surgery. There is increasing need to develop the potential and relevance of day case surgery in developing countries which may result in substantial economic benefits. The health sectors in developing countries are coping with scarce resources and therefore day case surgery is an economically better option providing more advantages to patients as well as stakeholders. Surgical societies in developing countries should work closely with the Associations of Surgery in developed countries to establish infrastructure and guidelines to promote day case surgery in developing countries in East Africa.